Simple hysterectomy in early-stage cervical cancer: is it the way forward? - Rashmi Bagga; Pradip Kumar Saha; Gaurav Khastgir; Anne Monga (Gynecology and Obstetrics Clinical Medicine)
AbstractThe recently published SHAPE trial demonstrated the non-inferiority of simple hysterectomy compared with its radical counterpart in the management of early-stage, low-risk cervical cancers. Additionally, the study found lower rates of urinary complications and improved sexual health outcomes with simple hysterectomy. There were similar rates of local recurrence with no significant increase in the need for postoperative radiotherapy. Although it may be difficult to depart from a well-established standard of treatment that has demonstrated good results throughout, the results of this trial demonstrate that some patients with low volume and small tumours might benefit from reducing surgical radicality. However, further studies would be necessary before gynaecological oncologists would be willing to sacrifice the greater oncological safety proven by radical hysterectomy and opt for simple hysterectomy instead. The study has its limitations with confounding factors and limited follow-up duration. Nonetheless, it highlights the need to develop new guidelines and recommendations for managing patients with early-stage cervical malignancies.